Contextualization of the Audit Benefit for Tax Returns - Jaider Granda Houses; Paola A. Carmona M; Lina M. Quiroz; Orlando Castellanos Polo (International Journal of Economics, Business Management and Accounting (IJEBMA), 2020)
It is essential to analyze the benefit of auditing in Colombia, review from when it began to be governed to date in order to contextualize and consolidate the information contained in the standard, giving the opportunity to understand in a simpler way the mechanism that is being used in tax returns. , for which it is intended to reduce the firmness times, the study is carried out in a toric way, asking about the edges that can be presented in various ways, the objective is to show and identify how and when it can be used in an appropriate way, to reach the conclusions the subject is structured in cases that occur in real life in which you can observe different scenarios that allow suggesting a correct use complying with the standard,At the end of all this analysis, a general panorama can be observed of how the benefit is being contributed at the country level